Environmental-friendly three-dimensional carbon nanotubes grown by soil clay and graphene oxide nanosheets for energy storage. (March 2022) - Hsu, Hao-Lin; Chiu, Wei-Cheng; Yang, Chih-Chiang; Chen, Lung-Chuan; Lin, Chun-Liang; Huang, Chao-Ming; Hou, Shuhn-Shyurng
Abstract: Environmental-friendly three-dimensional (3D) multiwalled carbon nanotubes (CNTs) grown from the montmorillonite (MMT) and graphene oxide (GO) without adding metal catalysts are the first investigation for the supercapacitor electrode application, which dramatically reduces the noble and rare metal needs. Growth mechanisms of as-synthesized CNT-based MMTs (MCNTs) and CNT-based GOs- (GCNTs) via thermal chemical vapor deposition are suggested that the Ni ion nuclear seeds are self-arranged and intercalated spontaneously into the substrate surfaces and template layers. In addition, the maximum energy densities of MCNT and GCNT electrodes are 63.8 Wh/kg at 0.02 kW/kg and 147 Wh/kg at 0.09 kW/kg, respectively. The electrochemical impedance spectroscopy spectrum exhibits the charge transfer resistance significantly decreases with fabricating 3D active composite materials, indicating the mass transfer limitation in the low-frequency area and the charge transfer of kinetic controlling in the high-frequency domain. The Bode-phase angle at 78.6° of the GCNT electrode indicates ideal capacitive behavior. Frequencies of MCNT and GCNT electrodes at a phase angle of 45° are 0.27 and 0.11 Hz, corresponding to the calculated time relaxation constants of 3.70 and 9.09, respectively. MCNT and GCNT composites are clear to enhance a more surface accessible region for electrolyte ions and electron conductivity with the increasing CNT content. After 2000 continuous cyclic voltammetry and galvanostatic charge-discharge cyclic experiments, specific capacitance retentions with a 5% error bar of 3D MCNT and GCNT electrodes achieve 122.3 and 75.2%, 127.6 and 85.3%, respectively. As both electrodes, less metal usage is friendly to the environment, and in addition, layered fabrication is beneficial for production and further follow-up recycle separation of energy devices. Non-blending 3D MCNT and GCNT composites possess the potential to be the prospective materials for further energy storage application. Graphical abstract: Image 1 Highlights: Environmental-friendly carbon nanotube (CNT)-based materials for energy storage, reducing the noble and rare metal usage dramatically. Non-blending CNTs grown by montmorillonite (MMT) and graphene oxide (GO) nanosheets without adding metal catalysts. Good capacitances and energy density of CNT-based MMT and CNT-based GO composite electrodes. High-specific capacitance retention of MCNT (122.3%) and GCNT (127.6%) electrodes after 2000 cyclic voltammetry cyclic experiments.